2002
DOI: 10.1017/s0952523802194156
|View full text |Cite
|
Sign up to set email alerts
|

Cholecystokinin-like immunoreactive amacrine cells in the rat retina

Abstract: High levels of endogenous cholecystokinin (CCK) are present in the rat retina (Eskay & Beinfeld, 1982), but the cellular localization and physiological actions of CCK in the rat retina are uncertain. The goals of this study were to characterize the cells containing CCK, identify cell types that interact with CCK cells, and investigate the effects of CCK on rod bipolar cells. Rat retinas were labeled with antibody to gastrin-CCK (gCCK) using standard immunofluorescence techniques. Patch-clamp methods were used … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 62 publications
0
7
0
Order By: Relevance
“…Finding out what neuromodulators are used by the ipRGC-coupled amacrine cells would provide insights into how these neurons might influence retinal physiology. At least eleven neuromodulators have been detected in displaced rat amacrine cells: cholecystokinin [46], corticotropin releasing factor [47], dopamine [14], epinephrine [48], neurokinin A and B [49], neuropeptide Y [50], nitric oxide [51], somatostatin [52], substance P [53], and vasoactive intestinal peptide [54]. We have shown that ipRGC-coupled rat amacrine cells are not dopaminergic (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Finding out what neuromodulators are used by the ipRGC-coupled amacrine cells would provide insights into how these neurons might influence retinal physiology. At least eleven neuromodulators have been detected in displaced rat amacrine cells: cholecystokinin [46], corticotropin releasing factor [47], dopamine [14], epinephrine [48], neurokinin A and B [49], neuropeptide Y [50], nitric oxide [51], somatostatin [52], substance P [53], and vasoactive intestinal peptide [54]. We have shown that ipRGC-coupled rat amacrine cells are not dopaminergic (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…al, 2011), VG3 ACs (C13: VGlut3 [Slc17a8]; Haverkamp and WĂ€ssle, 2004;Johnson et al, 2004;Krishnaswamy et al, 2015); and A17 ACs (C6: Prkca (PKCα), Sdk1, Calb2 negative, Dab1-negative; Grimes et al, 2010;Puthussery and Fletcher 2007;Yamagata and Sanes, 2019). Other types expressed neuropeptides known to mark specific AC types; they include Cck (C10,C17,C18,C34; Firth et al, 2002), Vip, (C22,C26,C47; Park et al, 2015;Akrouh and Kerschensteiner, 2015;PĂ©rez de Sevilla MĂŒller et al, 2019), Crh (C37; Park et al, 2018) and Penk (C35,C59,C63; Chen et al, 2013). For some of these types, we were able to validate new markers, such as Car3 for VG3 cells (Figure 3B,C).…”
Section: Correspondence Between Clusters and Ac Typesmentioning
confidence: 86%
“…, 2008). Both CCK and the CCK‐B receptor have also been reported to be expressed in the retina, most likely in a subtype of amacrine cells (Firth et al. , 2002; Bragado et al.…”
Section: Discussionmentioning
confidence: 99%